1988
DOI: 10.2466/pms.1988.67.2.671
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Aerobic Fitness on Ratings of Perceived Exertion during Light to Moderate Exercise

Abstract: Based on scores from a maximal exercise test on a bicycle ergometer, 24 college-age women were classified into three aerobic-fitness groups. Each subject then completed two randomly ordered cycle exercise bouts at 1-wk. intervals. The exercise bouts required the subjects to pedal for 24 min. attaining and then maintaining a target heart rate of either 30% or 60% of heart-rate reserve. Ratings of perceived exertion (RPE) were reported at the end of each third minute of the exercise period. Repeated-measures ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 8 publications
6
12
0
Order By: Relevance
“…This concurs with previous research which shows that the prediction of _ VO 2 max from perceptually-regulated GXTs is not moderated by gender (Eston et al 2006). The results also support research that has demonstrated that high-and low-active individuals report similar RPEs at relative exercise intensities (Felts et al 1988;Parfitt et al 1996). We also provide further evidence that the theoretical maximal RPE of 20 is infrequently reported at volitional exhaustion, which concurs with previous research (St Clair Gibson et al 1999;Kay et al 2001;Eston et al 2007b).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This concurs with previous research which shows that the prediction of _ VO 2 max from perceptually-regulated GXTs is not moderated by gender (Eston et al 2006). The results also support research that has demonstrated that high-and low-active individuals report similar RPEs at relative exercise intensities (Felts et al 1988;Parfitt et al 1996). We also provide further evidence that the theoretical maximal RPE of 20 is infrequently reported at volitional exhaustion, which concurs with previous research (St Clair Gibson et al 1999;Kay et al 2001;Eston et al 2007b).…”
Section: Discussionsupporting
confidence: 94%
“…The influence of fitness, activity and athletic experience on the application of the RPE has been equivocal, with some studies reporting that fit individuals report lower RPE values (Hassmen 1990;Travlos and Marisi 1996), or no difference in RPE values (Demello et al 1987;Felts et al 1988;Mihevic 1983;Parfitt et al 1996;Winborn et al 1988) when compared to unfit individuals. Previous research has also provided inconsistent evidence regarding the influence of gender on the use of the RPE (Demello et al 1987;Eston et al 1987Eston et al , 2006Parfitt et al 1994;Purvis and Cureton 1981).…”
Section: Introductionmentioning
confidence: 95%
“…The study also supports previous research which indicates that the RPE O is not moderated by gender (DeMello et al 1987;Eston et al 1987Eston et al , 2006 or fitness (Felts 1988). The results provide further evidence that RPE O is as good as, or better than RPE P when reporting perceived exertion during a graded exercise test on a cycle ergometer to volitional exhaustion, as there was a greater consistency in the results of RPE O .…”
Section: Discussionsupporting
confidence: 90%
“…Fit individuals have been reported to exhibit lower RPE (DeMello et al 1987;Hassmen 1990;Travlos and Marisi 1996) or no difference in RPE (Mihevic 1983;DeMello et al 1987;Felts et al 1988;Winborn et al 1988) when compared with unfit individuals at a given relative exercise intensity. Travlos and Marisi (1996) observed that highly fit individuals (>56 ml kg À1 min À1 ) reported lower RPE than individuals who were low in fitness (<46 ml kg À1 min À1 ) at 10-min workloads on a cycle ergometer corresponding to equivalent exercise intensities of 40, 50, 60, 70 and 80% of _ VO 2max : Conversely, Mihevic (1983) reported that there are no differences in RPE between groups of high and low fitness during short duration, low-moderate exercise intensities.…”
Section: Introductionmentioning
confidence: 95%
“…Another important finding in our study pertains to the significant correlations of power, VO 2 and HR with RPE-L and RPE-D, as they confirm the association of RPE with cardiopulmonary responses and workout intensity. These findings corroborate those of Felts et al 26 , who found a significant relation between RPE and workout load and duration. However, it is important to highlight that the correlations found in the CADb-G were not as strong as those found in the other groups.…”
Section: Discussionsupporting
confidence: 83%